Electorality: formal device and effect (affection) of meaning - Quezada-Macchiavello, Óscar (1986)
The theoretical approach that I present below has as its object to delineate pertinent features of the electorality as a formal device and an intertextually produced effect. The enunciator will appear in the pragmatic space as long as it is observed, actorialized (when the simulation of its doing is constructed in the text). On the other hand, it will also be in the cognitive space of observation if it is implicit as a point of view before what is narrated. This is how the discursive device of the electoral situation confronts, at different levels, observation spaces and observed spaces.